New reading - B. F. Aparin (Бюллетень Почвенного института им. В.В. Докучаева, 2020)
The article provides the summary analysis of the content of the monograph “Soils of the Republic of Belarus” published in 2019 in Minsk. The book is a synthesis of the main achievements of scientific thought in the field of theoretical and applied soil science. It represents the new reading of the accumulated works over the past 40 years in the field of genetic research, soil mapping and land assessment. The monograph “Soils of the Republic of Belarus” will attract a lot of attention of specialists and scientists of various natural science profiles, as well as of practitioners who constantly work in the field.